1200 MPa high-formability complex-phase steel with aluminum-silicon coating and preparation method of 1200 MPa high-formability complex-phase steel

By optimizing chemical composition and process design and using aluminum-silicon plating technology, the problem of zinc atom embrittlement and insufficient corrosion resistance after welding of high-strength composite steel is solved, and high elongation, porosity and corrosion resistance are achieved. Improved, suitable for the high-forming needs of automotive parts.

CN119144902AInactive Publication Date: 2024-12-17ANGANG STEEL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411209538.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the welding process, zinc atoms enter the matrix, causing liquid metal embrittlement, and insufficient corrosion resistance, making it difficult to meet the high corrosion resistance requirements of automotive parts.

Method used

Using aluminum-silicon plating 1200MPa high-forming composite steel, the high elongation, pore reaming performance and surface quality of the steel plate are achieved through optimizing chemical composition and process design, combining aluminum-silicon plating solution composition and hot dipping process, including smelting and hot rolling , pickling, cold rolling, continuous retraction and aluminum-silicon plating and other processes.

Benefits of technology

The tensile strength of the steel plate is achieved above 1200MPa, the yield strength is 950~1150MPa, the elongation is ≥12%, and the porosity is ≥50%. The corrosion resistance and surface quality of the steel plate are improved through aluminum-silicon plating, and the zinc plating is solved. The problem of plasticity decrease after welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144902A_ABST
    Figure CN119144902A_ABST
Patent Text Reader

Abstract

The invention relates to 1200MPa high-formability complex-phase steel with an aluminum-silicon coating and a preparation method of the 1200MPa high-formability complex-phase steel. A base plate comprises the following chemical components in percentage by weight: 0.18-0.22% of C, 0.4-0.8% of Si, 2.0-2.4% of Mn, less than or equal to 0.02% of P, less than or equal to 0.006% of S, 0.2-0.5% of Mo, 0.3-0.5% of Cr, 0.03-0.06% of Ti, 0.03-0.06% of Cu and the balance of Fe and inevitable impurities, through the ingenious process design and the aluminum-silicon plating solution, the high-formability complex-phase steel with good mechanical property, reaming property and excellent surface quality is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of automobile steel manufacturing, and in particular relates to an aluminum-silicon coated 1200MPa high-formability complex phase steel and a preparation method thereof. Background Art

[0002] In recent years, the proportion of high-strength steel used in car bodies has gradually increased to reduce the weight of the car body and reduce energy consumption. Among many high-strength steels, complex phase steel has high flanging performance for the production of complex roll-formed parts, and is widely used in B-pillars, seat rails, chassis suspension parts, etc. As the service life of automobiles increases, higher requirements are placed on the corrosion resistance of automotive parts. At present, high corrosion-resistant complex phase steels are usually galvanized or zinc-aluminum-magnesium on the surface to achieve corrosion resistance. As zinc resources are increasingly scarce and zinc atoms enter the matrix during welding, liquid metal embrittlement will occur, causing parts to fail. Therefore, while ensuring that the mechanical properties and local flanging performance are not reduced, significantly improving the corrosion resistance of cold-rolled complex phase steel is an important research direction for increasing the added value of complex phase steel.

[0003] The Chinese patent application with publication number 201811621827.9 discloses a cold-rolled complex phase steel with a tensile strength of 1200MPa and a manufacturing method thereof. The composition design adopts a low carbon equivalent design. In the strip annealing process, it is heated to 760-830℃, slowly cooled to 670-730℃, and isothermally aged at 240-280℃. The mechanical properties of the steel plate are tensile strength of more than 1200MPa, yield strength of more than 900MPa, and elongation after fracture of more than 5%. The patent does not involve hole expansion performance and is a cold-rolled product, and does not involve surface coating.

[0004] The Chinese patent application with publication number 202110680950.3 discloses a 1200MPa grade enhanced forming complex phase steel and its preparation method. The chemical composition of the enhanced forming complex phase steel is as follows: C: 0.21-0.24%, Si: 1.0-1.4%, Mn: 2.1-2.6%, P≤0.01%, S≤0.005%, Cr: 0.4-0.7%, Nb: 0.02-0.04%, strengthening elements, and the rest is Fe and unavoidable impurities. The yield strength of the complex phase steel is 951-1148MPa, the tensile strength is 1201-1344MPa, the elongation after fracture is 6-10%, and the hole expansion rate is 40-59%. The product described in the patent is a cold-rolled product and does not involve surface coating.

[0005] The Chinese patent application with publication number 202110695244.6 discloses a 980MPa grade galvanized complex phase steel and its preparation method. The chemical composition of the galvanized complex phase steel is as follows: C: 0.1-0.12%, Si: 0.5-1.0%, Mn: 2.0-2.5%, Alt: 0.03-0.1%, Ti: 0.03-0.04%, P≤0.01%, S≤0.01%, N≤0.04%, and the balance is Fe and trace elements. The tensile strength of the complex phase steel is greater than 980MPa, the yield strength is greater than 780MPa, and the A50 elongation is greater than 14%. The product described in the patent is a hot-dip galvanized product, and there is liquid metal embrittlement during welding; for the production of higher strength parts, this steel plate is difficult to meet. Summary of the invention

[0006] In view of the above existing problems, the present invention provides a high-formability complex phase steel with an aluminum-silicon coating of 1200MPa and a preparation method thereof. Through ingenious process design and aluminum-silicon plating solution composition design, a high-formability complex phase steel with good elongation and hole expansion performance and high surface quality is achieved.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A high-formability composite steel with an aluminum-silicon coating of 1200MPa, wherein the chemical composition of the substrate is calculated by weight percentage as follows: C 0.18%-0.22%, Si 0.4%-0.8%, Mn 2.0%-2.4%, P≤0.02%, S≤0.006%, Mo 0.2%-0.5%, Cr 0.3%-0.5%, Ti 0.03%-0.06%, Cu 0.03%-0.06%, wherein: 0.6%≤Mo+Cr≤0.9%, the remainder being Fe and unavoidable impurities; the steel has a tensile strength of more than 1200MPa, a yield strength of 950-1150MPa, an elongation of ≥12%, and a hole expansion rate of ≥50%.

[0009] According to the plane area method, the structure of the steel includes: critical zone ferrite is 13% to 17%, epitaxial ferrite is 11% to 15%; bainite content is 35% to 42%; martensite content is 18% to 25%; residual austenite content is 5% to 10%.

[0010] The alloy design reasons of the present invention are as follows:

[0011] C: Carbon is the most economical strengthening element, ensuring the strength of the steel plate, and can make the material strength level reach 1200MPa. At the same time, it ensures that there is 5% to 10% residual austenite in the steel, which enhances the forming performance of the complex phase steel. However, too high a carbon content will inhibit the transformation of bainite and increase the hardness difference of each phase; too low a carbon content will make the stability of the undercooled austenite of the steel plate poor, making it difficult to store at room temperature. Therefore, the present invention controls the C content to 0.18% to 0.22%.

[0012] Si: Silicon can be dissolved in ferrite to strengthen ferrite. Si helps to discharge C into austenite and increase the stability of supercooled austenite. However, too high Si content will inhibit the precipitation of cementite in the over-aging stage, forming a high-hardness martensite phase, which is not conducive to the hole expansion performance of the steel plate. Therefore, the present invention controls the Si content to 0.4% to 0.8%.

[0013] Mn: Manganese is an austenite stabilizing element, has a significant solid solution strengthening effect on high-strength steel, can significantly improve the hardenability of steel, delay the pearlite transformation during the cooling process, and is the main strengthening element except carbon. When the manganese content is too low, the stability of the residual austenite is poor; and when the manganese content is too high, it will form MnS inclusions with S, causing hot brittleness of steel and deteriorating the processing properties of the material. Therefore, the present invention controls the Mn content to 2.0% to 2.4%.

[0014] P: Phosphorus is a harmful element in steel, and the lower its content, the better. Considering the cost, the content of P in the present invention is controlled to P≤0.02%.

[0015] S: Sulfur is a harmful element in steel, and the lower its content, the better. Considering the cost, the content of S in the present invention is controlled to S≤0.006%.

[0016] Mo: Mo is an element that improves hardenability, delays pearlite transformation, promotes bainite transformation, and is beneficial to improving the strength and formability of complex phase steel. Too much Mo element will segregate in ferrite and deteriorate ductility. The cost of Mo element is relatively high, so the present invention controls the Mo content to 0.2% to 0.5%.

[0017] Cr: Chromium is an element that improves hardenability, thereby ensuring that the steel obtains a sufficient amount of martensite to ensure strength. Cr is an element that expands the ferrite region. Too much Cr will reduce the two-phase region and increase the annealing temperature. Therefore, the present invention controls the Cr content to 0.3% to 0.5%.

[0018] Ti: Titanium is a microalloying element added to steel, which can combine with C and N atoms in steel to form fine dispersed precipitates TiC and TiN, thereby improving the strength of steel. However, excessive precipitation growth will reduce the formability of the material, so the present invention controls the Ti content to 0.03% to 0.06%.

[0019] Cu: Copper has good aging strengthening ability. Nano-scale Cu precipitates can effectively strengthen ferrite. During the annealing and aging insulation stage of the strip steel, Cu can effectively produce aging strengthening effects and prevent TiC and TiN from coarsening. In addition, Cu is added in combination with Cr and Mo to improve the corrosion resistance of the steel plate to a certain extent. However, excessive Cu will increase the brittleness of the steel and cause serious edge cracking during cold rolling. Therefore, the present invention controls the Cu content to 0.03% to 0.06%.

[0020] A method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa, comprising a series of processes including smelting, hot rolling, pickling, cold rolling, continuous annealing, and skin finishing; specifically comprising the following steps:

[0021] 1) Smelting: Smelting is performed by a converter to obtain an alloy composition within the above range.

[0022] 2) Hot rolling: The heating temperature is between 1220 and 1250℃ to ensure the precipitation of Ti atoms and have a good N fixation effect on the steel plate. The precipitation of Ti (C, N) at this stage can effectively pin the original austenite grain boundary and refine the original austenite grain boundary. The rough rolling temperature is between 1100 and 1150℃. In this temperature range, the dynamic recovery of austenite grains is promoted and the austenite recrystallization in the finishing rolling stage is promoted. The finishing rolling temperature is 1050 to 1100℃. At this stage, strain-induced precipitation of Ti (C, N) pins the original austenite grain boundary and refines the grains. The coiling temperature is between 600 and 650℃, and the coiling structure is ferrite + bainite. Too high a coiling temperature will cause coil collapse, and low a coiling temperature will cause difficulty in cold rolling. The final hot-rolled plate thickness is 2.8 to 3.2 mm.

[0023] 3) Pickling: Remove the iron oxide scale generated on the hot-rolled surface to ensure the surface quality of the cold-rolled steel plate. The pickling temperature is 75-90℃.

[0024] 4) Cold rolling: The cold rolling reduction rate is 50% to 60%, ensuring that the cold rolling reduction is more than 50%, promoting tissue fibrosis in the cold rolling configuration, and increasing energy storage; at the same time, preventing the cold rolling reduction rate from being too high, resulting in excessive deformation resistance and difficulty in rolling to the target thickness.

[0025] 5) Continuous retreat:

[0026] a) The heating temperature is 800-870°C, the isothermal time is 90-150s, the slow cooling temperature is 670-700°C, and the slow cooling rate is controlled at 2-6°C;

[0027] b) Aluminum-silicon plating: After slow cooling, keep the steel plate isothermal at 670-700℃ for 3-10s and then immerse it in aluminum-silicon liquid to plate the steel plate surface;

[0028] Then immerse the steel plate in aluminum silicon liquid to plate the surface;

[0029] c) After aluminum silicon plating, cool to 320-350°C at a cooling rate greater than 25°C / s and keep warm for 350-500s, then cool to room temperature at a cooling rate greater than 10°C / s.

[0030] The mechanism is: heating to 800-870°C, organizing most of the austenite structure or the full austenite structure, and obtaining a certain proportion of critical zone ferrite and austenite. If the heating temperature is too high, the austenite grains will grow, affecting the performance of the steel; if the heating temperature is too low, the degree of austenitization will be low, and it will be difficult to obtain a sufficient amount of martensite in the subsequent cooling process, making it difficult to ensure the strength of the steel. Slowly cool to 670-700°C for aluminum silicon plating, and this process generates a certain amount of ferrite. Since the hot-dip aluminum silicon is in the slow cooling stage, the temperature of the over-aging stage of the present invention can be flexibly adjusted according to the phase transformation point, breaking the limitation that traditional hot-dip galvanized steel sheets must be over-aged at high temperature for a short time, and can make the bainite transformation sufficient, which is beneficial to improve the hole expansion performance of complex phase steel. After aluminum silicon plating, cool to 320-350°C at a cooling rate greater than 25°C / s and keep warm. This process obtains a certain amount of bainite / martensite. If the temperature is lower than 320℃, the bainitic ferrite content in the structure is low, the martensite content is high, and the residual austenite stability is poor. In the subsequent cooling process, the residual austenite undergoes phase transformation, which reduces the elongation of the material. If the temperature is higher than 350℃, the bainitic ferrite content in the structure is high and the martensite content is low, and the strength of the material cannot be guaranteed to be 1200MPa. Keeping warm for a certain period of time promotes the balance of elements in the structure and the diffusion of C atoms in bainitic ferrite into supercooled austenite, increases the stability of supercooled austenite, and prevents phase transformation during the subsequent cooling.

[0031] 6) Skin finishing: The steel plate enters the skin finishing machine for plate shape adjustment, and the skin finishing elongation is 0.2% to 0.4%. The upper and lower surface roughness of the steel plate is 0.8 to 1.5 μm.

[0032] Finishing is a means to obtain a suitable surface roughness of the strip steel surface. The appropriate roughness range is helpful for the subsequent steel plate coating process. If the flattening elongation is too small, the strip steel surface will be rough and small; if the flattening elongation is large, the strip steel surface will be rough. In addition, if the flattening elongation is too large, the retained austenite will undergo martensitic transformation, which will reduce the formability of the strip steel.

[0033] The aluminum silicon plating solution has the following components by weight: Al content is 87% to 93%, and Si content is 7% to 13%.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1) The chemical composition of the steel of the present invention mainly contains C and Mn as the main elements, without obvious precious elements. Cr and Mo elements are added to obtain a certain amount of bainitic ferrite, reduce the hardness difference between ferrite and martensite, and ensure the hole expansion performance of the complex phase steel; a trace amount of Cu is added to precipitate a nano-scale precipitate phase, which not only ensures the strength of the material, but also improves the corrosion resistance of the material itself.

[0036] 2) The present invention adopts a novel hot-dip aluminum-silicon method to achieve high surface quality and corrosion resistance of complex phase steel, and cleverly coats aluminum-silicon in the slow cooling stage, breaking the limitation that traditional galvanized steel sheets must be aged at high temperature for a short time, which is beneficial to bainite transformation and improves the hole expansion performance of complex phase steel.

[0037] 3) The present invention innovatively proposes a hot-dip aluminum-silicon layer and its production process, which solves the problem of failure of galvanized complex phase steel due to decreased plasticity after spot welding.

[0038] 4) The final structure of the steel plate of the present invention is 13% to 17% of intercritical ferrite, 11% to 15% of epitaxial ferrite, 35% to 42% of bainite, 18% to 25% of martensite, 5% to 10% of residual austenite, and aluminum silicon coating on the steel surface. The present invention adopts a novel hot coating process to match the heat treatment system to obtain a new type of high-formability complex phase steel. The tensile strength of this complex phase steel is above 1200MPa, the yield strength is 950 to 1150MPa, the elongation is 12% to 15%, and the hole expansion rate is ≥50%. It is particularly suitable for automotive parts with a flanging and hole expansion design that require the steel plate to have high formability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the organizational morphology diagram of Example 1. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the specific implementation methods of the present invention are further described below in conjunction with embodiments. The following embodiments are used to specifically illustrate the contents of the present invention. These embodiments are only general descriptions of the contents of the present invention and do not limit the contents of the present invention.

[0041] Table 1 lists the chemical composition and plating solution composition of the example steel, Table 2 lists the rolling process parameters of the example steel, Table 3 lists the process parameters of the continuous annealing of the example steel, Table 4 gives the structure of the example steel, and Table 5 gives the mechanical properties of the example steel.

[0042] Table 1 Chemical composition of steel and plating solution composition, wt%

[0043]

[0044]

[0045] Table 2 Rolling process of example steel

[0046]

[0047] Table 3 Example steel annealing process

[0048]

[0049] Table 4 Structure of Example Steel (%)

[0050]

[0051] Table 5 Mechanical properties of example steel

[0052] Example Rp0.2 / MPa Rm / MPa <![CDATA[A 50 / %]]> λ / % 1 1082 1224 13.2 51.5 2 1063 1237 12.6 51.9 3 1039 1204 14.1 54.3 4 1046 1218 13.5 52.5 5 1140 1253 12.4 53.8 6 1021 1219 12.9 52.4 7 1054 1225 13.0 51.5 .

Claims

1. A high-formability composite steel with an aluminum-silicon coating of 1200 MPa, characterized in that: The chemical composition of the substrate is calculated by weight percentage as follows: C 0.18%-0.22%, Si 0.4%-0.8%, Mn 2.0%-2.4%, P≤0.02%, S≤0.006%, Mo0.2%-0.5%, Cr 0.3%-0.5%, Ti 0.03%-0.06%, Cu 0.03%-0.06%, wherein: 0.6%≤Mo+Cr≤0.9%, and the balance is Fe and unavoidable impurities.

2. The aluminum-silicon coated 1200MPa high-formability complex phase steel according to claim 1, characterized in that: The tensile strength of the steel is above 1200MPa, the yield strength is between 950 and 1150MPa, the elongation is ≥12%, and the hole expansion rate is ≥50%.

3. The aluminum-silicon coated 1200MPa high formability complex phase steel according to claim 1, characterized in that: According to the plane area method, the structure of the steel includes: critical zone ferrite is 13% to 17%, epitaxial ferrite is 11% to 15%; bainite content is 35% to 42%; martensite content is 18% to 25%; residual austenite content is 5% to 10%.

4. A method for preparing the aluminum-silicon coated 1200 MPa high formability complex phase steel according to any one of claims 1 to 3, comprising: A series of processes including smelting, hot rolling, pickling, cold rolling, continuous annealing and skin finishing; characterized in that the continuous annealing process specifically includes the following steps: 1) The heating temperature is 800-870°C, the isothermal time is 90-150s, the slow cooling temperature is 670-700°C, and the slow cooling speed is controlled at 2-6°C; 2) Aluminum-silicon plating: After slow cooling, the steel plate is immersed in aluminum-silicon liquid for 3 to 10 seconds at 670 to 700 °C for immersion plating; 3) After aluminum silicon plating, cool to 320-350°C at a cooling rate greater than 25°C / s and keep warm for 350-500s, then cool to room temperature at a cooling rate greater than 10°C / s.

5. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The hot rolling process includes: a heating temperature between 1220 and 1250°C, a rough rolling temperature between 1100 and 1150°C, a finishing rolling temperature between 1050 and 1100°C, and a curling temperature between 600 and 650°C.

6. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The final hot rolled plate thickness is 2.8 to 3.2 mm.

7. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The pickling process includes: the pickling temperature is 75-90°C.

8. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The cold rolling process includes: the cold rolling reduction rate is 50% to 60%.

9. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The finishing process includes: the finishing elongation is 0.2% to 0.4%.

10. The method for preparing a high-formability composite steel with an aluminum-silicon coating of 1200 MPa according to claim 4, characterized in that: The aluminum silicon plating solution has the following components by weight percentage: Al content is 87% to 93%, Si content is 7% to 13%, and the upper and lower surface roughness of the steel plate is 0.8 to 1.5 μm.

Citation Information

Patent Citations

  • Tensile strength-1200 MPa cold-rolled complex phase steel and preparation method thereof

    CN109778062A

  • 1200MPa-grade reinforced forming complex-phase steel and preparation method thereof

    CN113528946A

  • 980 MPa-grade galvanized complex-phase steel and preparation method thereof

    CN113528978A

  • Formed reinforced complex phase steel and preparation method thereof

    CN112251668A

  • High-reaming high-plasticity 980MPa-grade dual-phase galvanized steel plate and preparation method thereof

    CN113416888A